2018
DOI: 10.3390/ma11091709
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Macroalgae Biochar Nanomaterials with Highly Efficient Adsorption and Photodegradation Ability

Abstract: In this study, carbonized kelp biochar (AKB) modified by KOH impregnation and photocatalytic Bi2MoO6/AKB composite (BKBC) nanomaterials were the first time successfully synthesized for efficient removal of dyes in aqueous solution. BET, XRD, FT-IR, and SEM were employed to characterize as-prepared samples. UV-vis and other test results indicated that the removal efficiency of methylene blue (MB) was 61.39% and 94.12% for BKBC and AKB, respectively, which was up to 13 times and 20 times higher in comparison wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…This is why, the parameters of the pseudo-second order model were used for the description and comparison of biosorption properties of Cladophora glomerata biochar. These results are in line with the data presented by Zhou et al (2018), who used the pseudo-first and pseudo-second order model for the description of biosorption kinetics of dyes (methylene blue) by biochar produced from waste kelp. It was shown that adsorption kinetics fitted well with a pseudo-second order model [12].…”
Section: Biosorption Properties Of Biocharssupporting
confidence: 91%
See 4 more Smart Citations
“…This is why, the parameters of the pseudo-second order model were used for the description and comparison of biosorption properties of Cladophora glomerata biochar. These results are in line with the data presented by Zhou et al (2018), who used the pseudo-first and pseudo-second order model for the description of biosorption kinetics of dyes (methylene blue) by biochar produced from waste kelp. It was shown that adsorption kinetics fitted well with a pseudo-second order model [12].…”
Section: Biosorption Properties Of Biocharssupporting
confidence: 91%
“…These results are in line with the data presented by Zhou et al (2018), who used the pseudo-first and pseudo-second order model for the description of biosorption kinetics of dyes (methylene blue) by biochar produced from waste kelp. It was shown that adsorption kinetics fitted well with a pseudo-second order model [12]. It was similar in the case of the sorption of Remazol dyes by biochar from green seaweed Ulva lactuca [37].…”
Section: Biosorption Properties Of Biocharssupporting
confidence: 91%
See 3 more Smart Citations